Understanding Gender Patterns in Knowledge, Attitudes, and Practices of Anemia Prevention Among Junior High School Students - Sheilla Rahma Niansyah; Bhakti Permana (STIKep PPNI Jawa Barat, 2026)
Background: Anemia remains a prevalent nutritional problem among adolescents, influenced by rapid growth, dietary patterns, and in females menstrual blood loss. Understanding whether gender differences exist in anemia-related knowledge, attitudes, and preventive practices is essential for designing effective school-based interventions. Objective: To describe and compare knowledge, attitudes, and preventive practices related to anemia among male and female junior high school students. Methods: A descriptive comparative study was conducted among 134 junior high school students (grades 7–9) in West Bandung, Indonesia. Participants were selected through random selection within classes at a single school. Knowledge, attitudes, and preventive practices were assessed using structured questionnaires. Gender differences were analyzed using the Mann–Whitney U test due to non-normal data distribution. Results: Female students demonstrated higher proportions in the high-knowledge category compared with males; however, the difference in knowledge scores between genders did not reach statistical significance (p = 0.060). No statistically significant gender differences were observed in attitudes (p = 0.160) or preventive practices (p = 0.285). Most students of both genders exhibited moderate attitudes and moderate anemia prevention practices. Conclusion: No statistically significant gender differences were identified in knowledge, attitudes, or preventive practices related to anemia among junior high school students. Although female students tended to show higher knowledge levels, this pattern represents a non-significant trend rather than a confirmed difference. These findings suggest that anemia prevention programs should target both male and female adolescents equally, with emphasis on translating knowledge into consistent preventive behaviors through comprehensive school-based interventions.